Impact of substitution among generic drugs on persistence and adherence: A retrospective claims data study from 2 Local Healthcare Units in the Lombardy Region of Italy. (June 2016) - Colombo, Giorgio L.; Agabiti-Rosei, Enrico; Margonato, Alberto; Mencacci, Claudio; Montecucco, Carlo Maurizio; Trevisan, Roberto; Catapano, Alberico L.
Abstract: Background: The use of generics, equivalent but less expensive drugs, is an important opportunity to reduce healthcare expenditure. Methods: The purpose of this study was to investigate the effect of substitution between unbranded generics on persistence and adherence to therapy in two Italian Local Health Units (ASL) in real-world clinical practice in 5 therapeutic areas using tracing drugs. Substitution of generic drugs is any change in the name of the manufacturer of the generic drug. The therapeutic areas were: diabetes (metformin); hypertension (amlodipine); dyslipidemia (simvastatin); psychiatry (sertraline); cardiology (propafenone); osteoporosis (alendronate). The retrospective analysis was carried out on the administrative databases of two Local Healthcare Units (ASL – Azienda sanitaria locale Bergamo (BG) and Pavia (PV)) in the Lombardy Region of Italy. The correlation between persistence and adherence with the different cohorts of generic substitution frequency within each therapeutic area was then calculated. Results: According to the inclusion criteria, 23, 773 patients were evaluated. Patients were observed for a period of 36 months starting from the first drug delivery (index date). The median age of the overall population was above 61 years in all therapeutic areas. The generic drug substitution occurred in 61.5% of patients (BG: 57.6% and PV: 65.4% respectively); Hypertension was the therapeutic area with the highest percentage of patients with substitutions. Patients' adherence, evaluated by the Medical Possession Rate (MPR) and persistence to the treatment decreases with the increase in the frequency of generic substitutions. This observation was confirmed by a statistically significant negative correlation (p-value of <0.001) between the adherence and persistence and the number of generic substitutions in each therapeutic area and Local Healthcare Units (ASL). Discussion: Adherence is one of the pillars of the patient's health management in the control and prevention of progression of the disease. Several factors, such as ageing, comorbidities, and polypharmacy, may affect adherence and influence the outcome of treatments. These results are in line with studies supporting the possibility that the change of package appearance each time a new prescription is dispensed may create confusion and ultimately reduce patients' adherence. Clinicians and decision makers should consider the impact of frequent generic substitutions on persistence and adherence, which may influence efficacy and/or safety.